Analisis Peluang, Ancaman, Solusi Perdagangan Internasional Indonesia-Singapura Sektor Perkebunan Kakao Tahun 2025 Berkelanjutan - Egi Nanda Pratama (CV. ITTC INDONESIA, 2026)
This study analyzes the opportunities, threats, and solutions in international trade within the cocoa plantation sector between Indonesia and Singapore in 2025. Indonesia, as one of the world’s leading cocoa producers, has significant export potential, while Singapore functions as a regional trade and re-export hub in Southeast Asia. The objective of this research is to examine the dynamics of cocoa trade, identify key challenges, and formulate strategic solutions to enhance competitiveness. This study employs a descriptive method with a mixed approach, combining quantitative data from the Central Statistics Agency (BPS) and qualitative data from relevant literature. The findings reveal that major opportunities include increasing global demand for cocoa-based processed products and the strengthening of bilateral trade cooperation. However, several threats persist, such as global price volatility, declining productivity due to pests and diseases, and strict international quality standards and export regulations. Additionally, competition from major cocoa-producing countries such as Ghana and Côte d’Ivoire poses further challenges. Recommended solutions include improving plantation productivity through replanting programs, implementing integrated pest management, enhancing downstream cocoa processing to increase value-added products, and strengthening certification and quality standards. These strategies are expected to improve Indonesia’s competitiveness and support sustainable trade relations with Singapore.